Statement of The expert council on acid-related diseases diagnostics and treatment - V. T. Ivashkin; Ye. K. Baranskaya; K. V. Ivashkin; N. V. Korochanskaya; O. V. Krapivnaya; T. L. Lapina; K. M. Nikolayeva; N. N. Nikolayeva; V. I. Simanenkov; A. S. Trukhmanov; I. B. Khlynov; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.